Edukasi Ergonomi Sebagai Upaya Pencegahan Gangguan Musculoskeletal Disorders Pada Perawat - Adhinda Putri; Idhar Darlis; Tenri Diah T.A; Sri Rezkiani Kas (Window of Community Dedication Journal, 2024)
Nurses are highly susceptible to work-related musculoskeletal disorders (MSDs). This is due to their role as an integral part of the healthcare team that serves to bridge communication between doctors and patients and facilitate the delivery of healthcare services in hospitals. Musculoskeletal disorders are one of the most frequently reported among various types of Occupational Diseases (PAK). The risk of Musculoskeletal Disorders (MSDs) can be predicted based on individual, psychosocial, and ergonomic factors. The purpose of this community service is to improve nurses' knowledge regarding ergonomics as an effort to prevent musculoskeletal disorders in nurses at RSUD Labuang Baji Makassar. The method used in implementing this socialization is the lecture method. The results of the t-test showed a significant influence on increasing the knowledge of nurses at RSUD Labuang Baji Makassar after being given education with a p-value =0.000.